Quality Characteristics of Raspberry Fruits from Dormancy Plants and Their Feasibility as Food Ingredients - Sílvia Petronilho; Manuel A. Coimbra; Cláudia P. Passos (Foods, 2023)
The raspberry (Rubus idaeus L.) is a soft red fruit consumed worldwide due to its bitter-sweet taste and phenolics-associated health benefits. During plant dormancy, raspberry fruits are discarded. However, this work hypothesised that these fruits have the chemical quality to be valorised, which would mitigate their waste if adequately stabilised. This can be achieved by drying. The Pacific Deluxe and Versailles varieties were dried by freeze- and convective-drying (30 °C and 40 °C). The freeze-dried fruits preserved their colour, drupelets structure, and phenolic content. Convective-drying promoted a significant fruit darkening, which was more evident at 30 °C due to the longer drying process, and a loss of drupelets structure. Both temperatures promoted a similar decrease in phenolic content, as determined by HPLC, although the ABTS●+ antioxidant activity at 40 °C was lower (IC50 = 9 compared to 13 μg AAE/mg dry weight). To incorporate dried raspberries into muffin formulations, while keeping their red colour, it was necessary to change the raising agent from sodium bicarbonate to baker’s yeast. Sensory analysis by a non-trained panel revealed good acceptance, showing that fresh or dried raspberry fruits from dormancy had suitable characteristics for use as food ingredients.